Bekerja Tetapi Tetap Miskin, Apakah Permasalahan Kemiskinan Multidimensi? - Salam, Abdus; Suwandana, Endan; Watekhi, Watekhi (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Working but still in poverty, is one of the phenomena of poor workers where they continue to work but their work does not guarantee them a better life. This study uses the concept of poverty from a monetary and multidimensional perspective. This study uses data from the March 2018 National Socioeconomic Survey (Susenas) and 2018 Village Potential Survey (Podes), and uses logistic regression to analyze whether the phenomenon of the working poor is a multidimensional poverty problem. The results of the study stated that poor workers have a close relationship with low education, millennial/young workers, a single parent, employees, a high number of jobs, do not have any health insurance, do not have access to information and communication technology, are not reachable by banking facilities, and migrant.